PENGEMBANGAN DETEKSI ONLINE GAS KARBONDIOKSIDA MENGGUNAKAN CO2 METER VOLTCRAFT CM-100 - Sri Handayani; Lazuardi Umar; Rahmondia Nanda Setiadi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
"> Air pollution is one of environmental contaminations occurred by various factors, outside and inside the room. Based on NIOSH (National Institute for Occupational Safety and Health), the safe level of Carbondioxide for humans is less than 1000 ppm. In this study one sample component is developed that can measure and monitor the levels of Carbondioxide, and a moisture level inside the room by online service. this uses a Carbondioxide meter and SHT11 sensor-based microcontroller ATmega8535. The development of Carbondioxide consists of two stages of process, namely, a design and construction of the air quality monitoring systems, and data acquisition. There are four scenarios for collecting data smoky weather, rain weather, measurements of carbon dioxide levels in the room with variations of ventilation and variations in the number of occupants in the room. The research sucsesfully designs the component. It can be seen from the amount of Carbondioxide stage and humidity levels. The amount of Carbondioxide concentration on the smoke state the maximum is 621 ppm while the minimum value is 426 ppm. For intersection of accupant and ventilation variable, the maximum and minimum Carbondioxide is 1535 ppm and 467 ppm respectively. The moisture measurement scenario with SHT11 sensor for smoky weather has maximum value at 83.9%, the moisture with a minimum is at 71.0%, on the rain weather maximum value obtained at 85.8% and 77.3% for minimum. While the occupant’s variation and variation of ventilation obtained maximum humidity value at 82.7% with a minimum value at 68.7%.